Identificación de ácaros productores de sarna en caninos en tres clínicas veterinarias de santander de quilichao - cauca (2022)
The identification of scabies-producing mites was carried out in the first half of 2022, in three veterinary clinics in the municipality of Santander de Quilichao (Cauca), where the respective diagnoses were made through deep skin scrapings of affected areas. Canine patients who came to the outpatient clinic with dermatological symptoms compatible with the presence of scabies during the study period were taken; In the San Gabriel veterinary clinic of the canines that showed dermatological problems compatible with the presence of scabies, 8 canines were analyzed, of which 62.5% (5) are between 0 and 1 year old, 12.5% (1) between 1 to 2 years and 25% (2) older than 2 years. Regarding sex, 50% were male and 50%. In the pet clinic, 11 canines were evaluated, of which 63.63% (7) were between 0 and 1 year old, 9% (1) between 1 and 2 years old, and 27.27% (3) older than 2 years old, in terms of sex 54.5% (6) were male and 45.5% (5) were female. In the Zoo Pets Veterinary Clinic, 4 canines with dermatological problems and/or presumptive symptoms of scabies were evaluated, of which 75% (3) were between 0 and 1 years old and 25% (1) between 1 and 2 years old. years, 50% were males and 50% were females. The San Gabriel clinic was found with an infestation of 37.5%, followed by the zoomascotas clinic with 25%, while the Pets clinic had an infestation of 18%. Demodex Spp was observed in the San Gabriel and Pet clinics, respectively, with an infestation of 25% and 18%, and Sarcoptes Spp in the San Gabriel and Zoomascotas clinics, with an infestation of 12.5% and 25%, respectively.